2017
DOI: 10.1002/bmc.3982
|View full text |Cite
|
Sign up to set email alerts
|

LC/QTOF profile and preliminary stability studies of an enriched flavonoid fraction of Cecropia pachystachya Trécul leaves with potential antidepressant‐like activity

Abstract: There is increasing interest in natural antioxidants that are candidates for the prevention of brain damage occurring in major depressive disorders. Cecropia pachystachya is a tropical tree species of Central and South America and a rich source of polyphenols, particularly flavonoids. The aim of this study was to characterize the flavonoid profile of an enriched flavonoid fraction of C. pachystachya (EFF-Cp) and evaluate the antidepressant-like effects of its acute administration in behavior, cytokine levels, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 67 publications
(89 reference statements)
3
17
0
Order By: Relevance
“…Phytochemical surveys already indicated the presence of several groups of flavonoids, tannins (Souza et al, 2014;Ortmann et al, 2016;Ortmann et al, 2017), and catechins (Costa et al, 2011;Cruz et al, 2013). High-performance liquid chromatographic analyses allowed the identification of the flavonoids C-glycosides including isoorientin, isovitexin, orientin, vitexin, and rutin (Costa et al, 2011;Brango-Vanegas et al, 2014), and chlorogenic acid (Brango-Vanegas et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical surveys already indicated the presence of several groups of flavonoids, tannins (Souza et al, 2014;Ortmann et al, 2016;Ortmann et al, 2017), and catechins (Costa et al, 2011;Cruz et al, 2013). High-performance liquid chromatographic analyses allowed the identification of the flavonoids C-glycosides including isoorientin, isovitexin, orientin, vitexin, and rutin (Costa et al, 2011;Brango-Vanegas et al, 2014), and chlorogenic acid (Brango-Vanegas et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have indicated a phenolic‐rich profile, which includes C ‐glycosylated flavonoids, such as orientin, isoorientin, vitexin and isovitexin, in addition to chlorogenic acid. These constituents have been related to biological properties, such as anti‐inflammatory, leishmanicidal, and hypoglycemic activities, among others . Cecropia hololeuca possesses silver leaves, and because of this, is popularly known in Brazil as silver embaúba .…”
Section: Introductionmentioning
confidence: 99%
“…The neuroprotective mechanisms of antidepressant effects remain to stay vague, in spite of the fact that it is proposed that flavonoids generally exert their antidepressant-like effects via altering behavior, cytokine levels, oxidative stress, and energy metabolism parameters. In addition to antioxidative action, each flavonoid follows its idiocratical one or more different pathways from these general routes against advancement and progression of depression including prevention of mitochondrial membrane potential dissipation, agonizing GABA-benzodiazepine receptors interaction with κ -opioid receptors and kynurenine pathway (KP), acetylcholinesterase activity regulation, helping to maintain brain plasticity, inhibition of L-arginine-NO, extracellular signal-related kinase (ERK) 1/2 and AKT phosphorylation pathways, modulation of intracellular calcium overload and K + channels, downregulation of Bax, caspases 3 and 9, and cytochrome C (Cyt-C) protein expression, and upregulation of Bcl protein expression were also afforded to positive impacts of flavonoids in the treatment depression [ 108 112 ].…”
Section: Resultsmentioning
confidence: 99%